Acupuncture Point Stimulation Treatments Combined With Conventional Treatment in Chronic Obstructive Pulmonary Disease: A Systematic Review and Network Meta-Analysis - Tsai, Cheng-Lin; Lan, Chou-Chin; Wu, Chih-Wei; Wu, Yun-Chun; Kuo, Chan-Yen; Tzeng, I-Shiang; Hsu, Pei-Shan; Lee, Chang-Ti; Hsieh, Po-Chun (Frontiers in Medicine, 2021)
Background Chronic obstructive pulmonary disease (COPD), which is a disease characterized by dyspnea, cough, and respiratory symptoms, leading to impaired health-related quality of life (HRQL) and exercise capacity, is highly prevalent worldwide. Some studies demonstrated that acupuncture point stimulation treatments (APSTs) are effective and safe in treating patients with COPD. The aim of this systematic review and network meta-analysis is to analyze the effects on HRQL and FEV1% predicted of diverse APSTs in treating patients with COPD. Materials and Methods We searched seven electronic databases. Randomized controlled trials (RCTs) with stable COPD patients comparing APSTs and conventional treatment (Tx) were included. The primary outcome was HRQL measured by COPD Assessment Test or St. George’s Respiratory Questionnaire. The secondary outcome was FEV1% predicted. We performed random effect network meta-analysis using a consistency model. Results This network meta-analysis analyzed 21 RCTs with 1577 stable COPD participants. In comparison with Tx, acupressure massage (AM) + Tx (-5.11; 95% confidence interval [CI], -6.65 to -3.57) was the most effective intervention in improving HRQL, followed by moxibustion (Mx) + Tx (-2.86; 95% CI, -3.86 to -1.86). Moreover, in comparison with Tx, Mx + Tx (7.79; 95% CI, 2.16 to 13.42) was the most effective intervention in improving FEV1% predicted, followed by acupuncture (A) + Tx (5.79; 95% CI, 2.90 to 8.68). Conclusions Combined interventions (APSTs + Tx) are more effective than single intervention in improving both HRQL and FEV1% predicted. AM, Mx, and A can be considered effective non-pharmacological complementary interventions in treating patients with COPD under Tx.